Food tourism policy: Deconstructing boundaries of taste and class. (June 2017) - de Jong, Anna; Varley, Peter
Abstract: Recent discussions from the journal of tourism management call for more critical deconstructions of the political and economic structures that shape policy and planning. The present paper takes up this call, using a post-structualist framework to examine Scotland's food tourism landscape. Utilising Foucauldian discourse analysis to deconstruct 2, 312 media sources collected through a Factiva database search, we illustrate how policy discourses privilege middle class cultural symbols through official food tourism promotion, marginalising particular foods positioned as working class. We find that this is particularly evident through the example of the deep fried mars bar; where, despite touristic desires, classed media discourses constructed it as global, bad and disgusting, and therefore an embarrassment to official tourism bodies. We conclude by discussing the broader importance of attending to the marginalising and silencing effects tourism policy exerts when the power values and interests involved in its formation are not critically appraised. Highlights: Scotland's food tourism landscape is assessed using a post-structualist approach. We reveal policy privileges middle class symbols, marginalising working class. Food tourism policy is shown to overlook complexity of touristic desire. A case is made for further deconstruction of food tourism policy.